Performance and NOx Investigation on Diesel Engine using Cold EGR Spiral Tube: A Review - Semin Semin; Adhi Iswantoro; Fatekhun Faris (International Journal of Marine Engineering Innovation and Research, 2017)
The world has the same problem to reduce emissions. Based the problem, many technologies invented to reduce the Emission. One of them is EGR (Exhaust Gas Recirculation). EGR is the most simpleNOx reduction by circulating potion of exhaust gas return into the combustion chamber. EGR system is often known by the name the hot EGR where exhaust gas circulation process without cooling system. This new Hot EGR system is designed by the addition of cooling system with air-cooled type. So that the circulating of exhaust gas to be cooled in advance in such that the mass of air increases.This research aims to study the performance and a reduction in NOX of diesel engine with EGR using addition of air cooling system. The experiments were used on diesel engine Yanmar TF 85-MHDI